PRIMARY SPONTANEOUS PARTIAL PNEUMOTHORAX IN A PATIENT WITH COVID-19 PNEUMONIA. HAVE WE UNDERESTIMATED THIS COMPLICATION? A CASE REPORT - Dmitrović, Radmila; Lazovic, Biljana; Esquinas, Antonio; Mulic, Mersudin (Sanamed, 2022)
Introduction and case report: We described a case of primary spontaneous partial pneumothorax in a middle-aged man with COVID-19 pneumonia who presented with fever, loss of appetite, and malaise. Laboratory results revealed higher levels of inflammatory markers, as well as sterile urine and blood cultures. On admission, a chest X-ray revealed bilateral patchy consolidations in the lung parenchyma, as well as a left-sided partial pneumothorax. Throughout his hospitalization, the patient was closely examined by a thoracic surgeon, and a chest X-ray was taken on multiple occasions. There was spontaneous resorption of air from the pleural space. Conclusion: Pneumothorax is a rare but serious complication of the COVID-19 infection that has recently been documented in patients with no comorbidities, requiring various types of ventilatory support. The precise mechanism of primary spontaneous pneumothorax in COVID-19 infection is unknown, but it will undoubtedly pose a challenge to future researchers.